Physiological index of seedlings of Coffea arabica grafted on Coffea canephora - Ferreira, André Dominghetti; Mendes, Antônio Nazareno Guimarães; Guimarães, Rubens José; Carvalho, Alex Mendonça de; Pinto, Marcelo Frota (Coffee Science - ISSN 1984-3909)
The analysis of growth is performed in order to explain the differences in growth of plants. This work had the objective of evaluating the development of C. arabica L. seedlings grafted with C. canephora Pierre ex Froehner. The experiment was performed in a greenhouse at the Federal University of Lavras using nutritive solution. There was used a factorial 7 x 3 + 2, with seven cultivars of C. arabica (Palma II, Catucaí 2SL, Oeiras MG 6851, Obatã IAC 1669-20, Acauã, Topázio MG 1190 and Paraíso MG H 419-1), three types of seedling (ungrafted, self-grafted and graft in the cultivar Apoatã IAC 2258) and two additional (Apoatã self grafted and Apoatã ungrafted). The results obtained showed that the grafting technique and the rootstock used did not interfere with the development of the plants, although C. arabica cultivars used showed development similar in all the three types of seedlings.